Novel sous-vide pressure technique affecting properties of local beef muscle - Natthaporn Chotigavin; William L. Kerr; Wanwimol Klaypradit; Soraya Kerdpiboon (My University, 2023)
The low-temperature, long-time method of cooking known as sous-vide was used with increased pressure to enhance the tenderness and cook yield of local Thai beef round. The cooking was done in specialized equipment at 60 °C and 101, 200 or 300 kPa for 0–4 h. Beef treated with pressure was slightly lighter in color, and samples cooked for 2 h at 200 kPa had greater red saturation. Cooking at 200 kPa improved cook yield while reducing cook loss, with values of 78% after 4 h at 200–300 kPa versus 67% at 101 kPa. Cooking at 200–300 kPa resulted in more tender beef than at 101 kPa after 2 h. Sensory evaluation showed sous-vide pressure beef had higher ranking scores for tenderness and juiciness compared to control. SEM showed connective tissue of sous-vide pressure-cooked beef was diffuse and with looser muscle fibers than boiled or raw beef. Electrophoretic profiles showed that thick and thin filament bands decreased with cooking time. However, myosin heavy chain was sensitive to both heat and pressure. Reducing conditions showed pressure and heat induced disulfide bonding. Studies by FTIR showed cooking at 200 kPa caused the greatest decrease in α-helix content and increase in β-structures than non-treated and boiled beef.
Keywords: Sous vide; Beef Cattle; Organoleptic; Meat and Animal Product Quality